Design of band-gap reference for high temperature application - Su, Zun Mon. (2012)
CMOS Band-gap reference circuits were designed in this project. Different approaches for the design are considered. In this project, the designs were simulated using 1.0 μm SOI-CMOS Technology from XFAB. XI10 from XFAB process is used. The sensitivity of threshold voltages and mobility of the MOSFET transistors had created challenging problems to achieve the good band-gap reference circuit.